Implementasi Permainan Tradisional Hadang Berbasis Outdoor Learning dalam Penguatan Literasi Gerak dan Kebugaran Remaja Pesisir - Ardin Gani; Iwan Fataha (Jambura Arena Pengabdian, 2026)
Traditional games, as part of local cultural heritage, have considerable potential to improve adolescents' physical activity, movement literacy, and social interaction. However, technological development and lifestyle changes have reduced young people's participation in traditional games, including the Hadang game. This community service program aimed to enhance adolescents' movement literacy through the implementation of a Hadang traditional game based on an outdoor learning approach in coastal communities of Gorontalo Province, Indonesia. The program employed a participatory approach consisting of preliminary observation, socialization, game demonstration, guided practice, mentoring, and evaluation. The target participants were coastal adolescents, while community leaders, youth organizations, and village officials were actively involved as community partners. Program evaluation was conducted using observation sheets, activity documentation, and participant response questionnaires to assess participation, movement skills, teamwork, communication, and enthusiasm throughout the activities. The results indicated that participants successfully understood the rules of the Hadang game, demonstrated greater engagement in physical activities, improved teamwork and communication skills, and expressed positive responses toward the program. In addition to strengthening movement literacy, the program contributed to preserving traditional games as a contextual outdoor learning strategy. The outputs included a guideline for implementing Hadang-based outdoor learning activities, activity documentation, and recommendations for integrating traditional games into community and school-based physical activity programs. This model has the potential to be replicated in other communities with similar environmental characteristics.